Effect of rock mass properties on skin friction of rock socket - Alias, Yusliza (2015)
Reliable design of foundation in rock requires an in depth knowledge on its mass properties. Most rock types exhibit high strength and therefore soketed bored pile is often the preferred method for foundation of major structures. However, in situ properties of a rock mass can be so much different from intact rock due to its discontinuous state. In addition, these in situ properties are difficult to determine reliably and this often leads to some degree of uncertainties in the design of the bored pile. Consequently, bearing capacity of the in situ rock is often being underestimated. The underestimation is mainly contributed by application of various reduction factors and correlations in the design process. For example ultimate skin friction (fs) and rock socket length (L) are determined empirically, which is based on rock mass properties which are indirectly estimated using intact rock properties. This study is to highlight the importance of obtaining reliable properties of the in situ rock mass for proper utilisation of the rock mass strength. Data obtained from in situ measurement on rock mass, namely in situ modulus (Em) and RQD, have been used to obtain a proper estimation of fs. To verify the positive contribution of these mass properties on the performance of bored pile, comparison was made with fs and L estimated using in situ measurement and empirical approach. Despite of limited field data, this study does indicate that design using rock mass properties from in situ measurement, gives a more reliable value of fs and L, as compared to the empirical approach. Field measurement such as Pressure meter test does help in obtaining a reliable rock mass properties consequently, this allows for effective utilisation of the rock mass strength as an effective foundation.